2016
DOI: 10.1186/s13000-016-0496-0
|View full text |Cite
|
Sign up to set email alerts
|

Serous carcinoma arising from uterine adenomyosis/adenomyotic cyst of the cervical stump: a report of 3 cases

Abstract: BackgroundSerous carcinoma arising in adenomyosis and adenomyotic cyst is very rare. Only 3 serous carcinomas and 5 serous endometrial intraepithelial carcinomas (EIC) have been reported to date.MethodsWe reviewed the clinicopathological features of 2 serous carcinoma in uterine adenomyosis and 1 serous EIC in adenomyotic cyst of the cervical stump.ResultsCase 1 had an endometrial serous carcinoma in the uterine myometrium and the left ovary. A minor component of benign endometrial glands with minimal endometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Little is known about the pathogenesis of EEC-AIA. The malignant transformation of adenomyosis is thought to be due to the transition of the endometrial epithelium into monolayer tumor cells 19 , which can produce many histological types, including EEC, papillary serous carcinoma 20 , serous carcinoma 21,22 , primary uterine müllerian mucinous borderline tumor (MMBT) 23 , and clear cell carcinoma 24 . The predominant histological types are EEC and clear cell carcinoma 7,25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the pathogenesis of EEC-AIA. The malignant transformation of adenomyosis is thought to be due to the transition of the endometrial epithelium into monolayer tumor cells 19 , which can produce many histological types, including EEC, papillary serous carcinoma 20 , serous carcinoma 21,22 , primary uterine müllerian mucinous borderline tumor (MMBT) 23 , and clear cell carcinoma 24 . The predominant histological types are EEC and clear cell carcinoma 7,25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Hernandez and Woodruff [39], for example, reported that they identified adenomyosis in 21 (10%) out of the 204 hysterectomies carried out for endometrial cancer between 1955 and 1974 and that 2 out of the 21 cases had atypical hyperplasia and 6 had adenocarcinoma in adenomyosis. Lu et al [67] argued that these criteria are too strict. Indeed, they would not apply to any of their 3 cases.…”
Section: Endometrial Cancer Arising Within Adenomyotic Focimentioning
confidence: 99%
“…Therefore, to better clarify this issue, we conducted a systematic review and meta-analysis, including all published papers on the WT1 immunohistochemical expression across all histotypes of endometrial carcinoma. The present paper included a total of 35 eligible studies with 52 datasets and 1616 patients for qualitative analysis [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%